Hubungan Self-Efficacy, Belief dan Motivasi dengan Kecemasan Mahasiswa dalam Pembelajaran Bahasa Inggris - Lufiana Harnany Utami; Linda Nurjati (Psympathic : Jurnal Ilmiah Psikologi, 2017)
Anxiety about English is still felt in the learner at the college level, especially in dealing with reading sources in English. This study aims to see how individual factors (self-efficacy, belief, and motivation) effect the anxiety experienced by students in learning English. Research design use correlational research involving 100 students at UIN Sunan Gunung Djati Bandung from psychology faculty and  faculty of education and teacher training. Sampling technique is using stratified random sampling. There are four instruments used which are Foreign Language Classroom Anxiety Scale, Children’s Self-efficacy Scale, The Beliefs about Language Learning Inventory (BALLI) and motivation in learning english instrument. Data is analysed using statistic analysis of multiple regression. Results show that this each following variables which are self-efficacy, belief, and motivation has significant correlation with anxiety in learning English. Besides, there is also significant correlation between self-efficacy, belief,  motivation and anxiety in learning English.